Non-tuberculous mycobacteria profiles and their anti-mycobacterial resistance at a major medical center in Lebanon - Araj, George F; Baba, Omar Z; Itani, Lina Y; Avedissian, Aline Z; Sobh, Ghena M (The Journal of Infection in Developing Countries, 2019)
Introduction: Infection with non-tuberculosis mycobacteria (NTM) has been on the rise globally causing a wide spectrum of respiratory and extrapulmonary infections in humans. Studies on these pathogens from the Middle-East including Lebanon are scarce. Methodology: This retrospective study addresses the approach used for investigation, speciation and antimicrobial resistance (AMR) profiles of recovered NTM isolates from respiratory sources at a major tertiary care center in Lebanon during two periods (2003-2007 and 2013-2017). Processing of specimens, culture and differentiation of recovered NTM isolates from Mycobacterium tuberculosis were done in-house according to standard procedures. Upon request, speciation and AMR testing were performed using molecular and broth dilution methods, respectively, at Mayo Medical Laboratories (Rochester, Minnesota, USA). Results: Among 108 NTM analyzed isolates, 8 species were revealed during the two periods: M. simiae (51% vs 61%), M. avium complex (MAC) (6 % vs 12%) M. fortuitum (12% vs 5%), M. gordonae (6% vs 5%), M. abscessus (6% vs 7%), M. immunogenum (12% vs 0%), M. szulgai (4% vs 0%) and M. peregrinum (0% vs 2%). M. simiae isolates showed high susceptibility (93%-96%) to amikacin and clarithromycin, but high resistance to rifampin, ethambutol, ciprofloxacin, rifabutin, linezolid, trimethoprim/sulfamethoxazole and moxifloxacin. MAC isolates were only susceptible to clarithromycin (86%). M. abscessus isolates were uniformly susceptible to amikacin (100%). Conclusion: The revelaed different NTM species, with predominance of M.simiae and various AMR profiles provide a current epidemiologic database and help guiding the selection of appropriate empirical therapy once the clinical relevance is established.